Surface roughness of packable composite resins polished with various systems - Borges, Alessandra Bühler [UNESP]; Marsilio, Ana Lucia [UNESP]; Pagani, Clóvis [UNESP]; Rodrigues, José Roberto [UNESP] (Wiley, 2004)
Purpose: The aim of this study was to evaluate the surface roughness of four packable composite resins, SureFil™ (Dentsply, Petrópolis, Rio de Janeiro, Brazil), Prodigy Condensable™ (Kerr Co., Orange, CA, USA), Filtek P60™ (3M do Brasil, São Paulo, Brazil), and ALERT® (Jeneric/Pentron, Inc., Wallingford, CT, USA) and one microhybrid composite resin (Filtek Z250™, 3M do Brasil) after polishing with four finishing systems. Materials and Methods: Twenty specimens were made of each material (5 mm in diameter and 4 mm high) and were analyzed with a profilometer (Perthometer® S8P, Perthen, Mahr, Germany) to measure the mean surface roughness (Ra). The specimens were then divided into four groups according to the polishing system: group 1 - Sof-Lex™ (3M do Brasil), group 2 - Enhance™ (Dentsply), group 3 - Composite Finishing Kit (KG Sorensen, Barueri, São Paulo, Brazil), and group 4 - Jiffy Polisher Cups® (Ultradent Products, Inc., South Jordan, UT, USA). The specimens were polished and then evaluated for Ra, and the data were subjected to analysis of variance, analysis of covariance, and Tukey's test (p = .05). Results: The mean Ra of SureFil polished with Sof-Lex was significantly lower than that of KG points. Prodigy Condensable polished with Enhance showed a significantly less rough surface than when polished with Sof-Lex. Filtek P60 did not exhibit a significant difference with the various polishing systems. For ALERT the lowest mean Ra was obtained with Sof-Lex and the highest mean Ra with KG points. Regarding Filtek Z250, polishing with KG and Jiffy points resulted in a significantly lower mean Ra than when polished with Enhance. Conclusions: Packable composite resins display variable roughness depending on the polishing system used; the Sof-Lex disks and Jiffy points resulted in the best Ra values for the majority of the materials tested.
Keywords: resin; analysis; analysis of variance; comparative study; composite material; data analysis; evaluation; measurement; multivariate analysis of covariance; surface property; Analysis of Variance; Composite Resins; Dental Polishing; Dental Restoration, Permanent; Image Processing, Computer-Assisted; Materials Testing; Surface Properties